2011
DOI: 10.1093/jaoac/94.1.201
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Laboratory Validated Method for the Generation of DNA Barcodes for the Identification of Fish for Regulatory Compliance

Abstract: The U.S. Food and Drug Administration is responsible for ensuring that the nation's food supply is safe and accurately labeled. This task is particularly challenging in the case of seafood where a large variety of species are marketed, most of this commodity is imported, and processed product is difficult to identify using traditional morphological methods. Reliable species identification is critical for both foodborne illness investigations and for prevention of deceptive practices, such as those where specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
155
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(159 citation statements)
references
References 1 publication
3
155
0
1
Order By: Relevance
“…In the iBOL system, a target gene region consisting of 648 to 655 bp starting near the 5' end of the mitochondrial cytochrome c oxidase subunit 1 was recommended for animal identification (Hebert et al, 2003). This region has been shown to reliably discriminate animals from fish (Handy et al, 2011) to mammal (Ivanova, Clare, & Borisenko, 2012). A few literature also showed that mini barcode 100 to 200 bp was more effective in obtaining DNA sequence information from specimens containing degraded DNA than full length barcode (Hajibabaei, Janzen, Burns, Hallwachs, & Hebert, 2006;Meusnier et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the iBOL system, a target gene region consisting of 648 to 655 bp starting near the 5' end of the mitochondrial cytochrome c oxidase subunit 1 was recommended for animal identification (Hebert et al, 2003). This region has been shown to reliably discriminate animals from fish (Handy et al, 2011) to mammal (Ivanova, Clare, & Borisenko, 2012). A few literature also showed that mini barcode 100 to 200 bp was more effective in obtaining DNA sequence information from specimens containing degraded DNA than full length barcode (Hajibabaei, Janzen, Burns, Hallwachs, & Hebert, 2006;Meusnier et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…So far, several studies in the application of DNA barcoding for food detection have been reported. Handy et al (2011) reported a single-laboratory validated barcoding method for fish identification. Jones, Peters, Weland, Ivanova, and Yancy (2013) reported the use of DNA barcodes for identification of hazard animals in relation to filth in food.…”
Section: Introductionmentioning
confidence: 99%
“…DNA barcoding is typically used by the U.S. Food and Drug Administration (FDA) to identify fish species in food for regulatory purposes (Handy et al, 2011). In DNA full-barcoding, a ∼650 base-pair (bp) region of the cytochrome c oxidase subunit 1 (CO1) gene is sequenced and compared to reference sequences to enable species identification.…”
Section: Introductionmentioning
confidence: 99%
“…Seafood authentication in food control laboratories can be carried out by a number of methods that include protein-based electrophoretic and mass spectroscopy techniques (Schiefenh€ ovel & Rehbein, 2013;Wulff et al, 2013;Carrera et al, 2014) or DNAbased methods (Lockley & Bardsley, 2000;Rasmussen & Morrissey, 2008;Handy et al, 2011). Moreover, the authorities or research institutions responsible for food quality assurances are often confronted with new imported food products.…”
Section: Introductionmentioning
confidence: 99%